2012
DOI: 10.1161/atvbaha.111.242073
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Acute Inhibitory Effect of Insulin on Chylomicron Production in Type 2 Diabetes

Abstract: Objective-Overproduction of intestinally derived apoB-48-containing triglyceride-rich lipoproteins (TRLs) (chylomicrons) has recently been described in type 2 diabetes, as is known for hepatic TRL-apoB-100 (very-low-density lipoprotein) production. Furthermore, insulin acutely inhibits both intestinal and hepatic TRL production, whereas this acute inhibitory effect on very-low-density lipoprotein production is blunted in type 2 diabetes. It is not currently known whether this acute effect on chylomicron produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…In presurgery, the mean TRL-apoB-48 FCR of SG and BP and mean TRL-apoB-48 PR of SG were in the range, whereas mean TRL-apoB-48 PR of BP was below the range when compared with those published in obese subjects. 9,49 After surgery, mean TRL-apoB-48 PR of SG was close to the mean TRL-apoB-48 PR of BP in presurgery and in the range of those of nonobese controls. 9,31 Despite no significant difference in presurgery between mean TRL-apoB-48 PR of SG and BP, the lower mean TRL-apoB-48 PR of BP compared with SG and to other studies of obese subjects might explain the absence of reduction in TRL-apoB-48 PR of BP after surgery.…”
Section: Discussionmentioning
confidence: 64%
“…In presurgery, the mean TRL-apoB-48 FCR of SG and BP and mean TRL-apoB-48 PR of SG were in the range, whereas mean TRL-apoB-48 PR of BP was below the range when compared with those published in obese subjects. 9,49 After surgery, mean TRL-apoB-48 PR of SG was close to the mean TRL-apoB-48 PR of BP in presurgery and in the range of those of nonobese controls. 9,31 Despite no significant difference in presurgery between mean TRL-apoB-48 PR of SG and BP, the lower mean TRL-apoB-48 PR of BP compared with SG and to other studies of obese subjects might explain the absence of reduction in TRL-apoB-48 PR of BP after surgery.…”
Section: Discussionmentioning
confidence: 64%
“…In such pathologies, the increased production of chylomicrons and their reduced clearance contribute to the postprandial dyslipidemia observed in insulinresistant individuals (38). The physiological suppressive effect of insulin on chylomicron production is reportedly absent in type 2 diabetes subjects (17). Duodenal explants from insulinresistant obese subjects undergoing bariatric surgery were shown to express higher mRNA levels of free fatty acid-binding proteins and MTP and to secrete more intestinal triglyceriderich lipoproteins, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several groups have reported that the intestine plays a role in the onset of insulin resistance in humans. Indeed, hyperinsulinemic insulin-resistant human subjects display increased production rates of intestinal apoB48-containing lipoproteins (16), and in individuals with type 2 diabetes, intestinal chylomicron production is resistant to insulin's acute suppressive effects (17).…”
mentioning
confidence: 99%
“…Similarly, acute elevation in FFA with intralipid and heparin increased TRL ApoB-48 production (42). In patients with type 2 diabetes, TRL ApoB-48 production is increased (65), and the acute suppressive effect of insulin on TRL ApoB-48 production is absent (110). In obese patients undergoing bariatric surgery, duodenal biopsies from insulin-resistant patients revealed reduced Akt phosphorylation and enhanced MAPK phosphorylation and increased lipogenesis and ApoB-48 biogenesis ex vivo compared to insulin-sensitive patients; these results were associated with increased expression of inflammatory markers and oxidative stress (159).…”
Section: Chylomicrons In Insulin Resistance and Type 2 Diabetesmentioning
confidence: 96%